Impact of Terrorism on Foreign Direct Investment: An Empirical Analysis of Pakistan - Ullah, Asad; Rahim, Asfandyar; Ali, Mohammad Daud; Khan, Shah Raza; Ali Shah, Syed Arshad (JISR management and social sciences & economics, 2021)
The purpose of this study is to find out the impact of Terrorism on FDI inflow in Pakistan as well as other variables such as economic growth, market size, trade openness and infrastructure. Using a simple regression model to estimate time series, annual data from 2001 to 2016, the study concludes that market size, economic growth, and trade openness have a significant positive relationship with FDI. At the same time, the result shows that Terrorism and infrastructure has a significant negative relationship with FDI. This empirically builds up the way that Terrorism is a real threat to FDI and economic development of the economies of Pakistan. The empirical outcomes of the study of Terrorism confirmed the way that Terrorism based oppression has harmed the economic prosperity of Pakistan and has debilitated FDI inflows during the sample period. Therefore, Pakistan will take to measures the investment environment in this area. Government strategy makers should consider the situation of Terrorism, instability and lawfulness circumstance to decrease the risk of investors and to ensure their investment ability to host FDI.